2010
DOI: 10.1901/jaba.2010.43-735
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Stimuli That Influence Compliance During the High‐probability Instruction Sequence

Abstract: When we evaluated variables that influence the effectiveness of the high-probability (high-p) instruction sequence, the sequence was associated with a precipitous decrease in compliance with high-p instructions for 1 participant, thereby precluding continued use of the sequence. We investigated the reasons for this decrease. Stimuli associated with the low-p instruction were systematically added and removed in the context of the high-p instructions, and results suggest that the stimuli associated with the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Recently, some authors have empirically examined the individual components that may be responsible for the effects of the high‐ p sequence (Normand, Kestner, & Jessel, ; Pitts & Dymond, ; Wilder, Majdalany, Sturkie, & Smeltz, ; Zuluaga & Normand, ). Generally, these studies suggest that a short inter‐instruction interval (Pitts & Dymond, ; Wilder et al, ), the delivery of preferred items for compliance with high‐ p instructions (Wilder et al, ; Zuluaga & Normand, ), and the presence of stimuli correlated with reinforcement for compliance with low‐ p instructions when delivering high‐ p instructions (Normand et al, ) are important components of the procedure. Interestingly, other studies in this general line of research suggest that the delivery of high‐ p instructions themselves may not be necessary to increase compliance (Bullock & Normand, ; Normand & Beaulieu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have empirically examined the individual components that may be responsible for the effects of the high‐ p sequence (Normand, Kestner, & Jessel, ; Pitts & Dymond, ; Wilder, Majdalany, Sturkie, & Smeltz, ; Zuluaga & Normand, ). Generally, these studies suggest that a short inter‐instruction interval (Pitts & Dymond, ; Wilder et al, ), the delivery of preferred items for compliance with high‐ p instructions (Wilder et al, ; Zuluaga & Normand, ), and the presence of stimuli correlated with reinforcement for compliance with low‐ p instructions when delivering high‐ p instructions (Normand et al, ) are important components of the procedure. Interestingly, other studies in this general line of research suggest that the delivery of high‐ p instructions themselves may not be necessary to increase compliance (Bullock & Normand, ; Normand & Beaulieu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Normand et al (2010) presented one of the few failures of the high-p (3) procedure with a typically developing preschooler who exhibited noncompliance when instructed to clean up preferred toys. Interestingly, the authors found that not only did compliance with the low-p remain low but also the participant began to exhibit noncompliance in the presence of the high-p instructions as well when signals were presented, indicating the eventual presentation of the low-p instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, high‐quality reinforcement should be delivered contingent on compliance with high‐p instructions (Wilder et al, ). Fourth, if the participant does not comply with high‐p instructions, stimuli associated with the low‐p instruction should be identified and eliminated (Normand et al, ), or other high‐p instructions should be used. Fifth, reinforcement should be delivered contingent upon compliance with the low‐p instruction.…”
Section: Recommendations For Practitionersmentioning
confidence: 99%
“…Other research has examined stimuli which influence compliance with high‐p instructions. Normand, Kestner, and Jessel () evaluated the high‐p sequence to increase compliance by a preschool boy. When the participant stopped complying with the high‐p instructions, the researchers removed a stimulus (a toy chest) associated with the low‐p instruction, “Put your toys away.” In the absence of the toy chest, compliance with high‐p instructions increased.…”
mentioning
confidence: 99%